2018
DOI: 10.1038/s41564-018-0245-0
|View full text |Cite|
|
Sign up to set email alerts
|

Mycobacterium tuberculosis carrying a rifampicin drug resistance mutation reprograms macrophage metabolism through cell wall lipid changes

Abstract: Tuberculosis is a significant global health threat, with one-third of the world's population infected with its causative agent Mycobacterium tuberculosis (Mtb). The emergence of multidrug-resistant (MDR) Mtb that is resistant to the frontline anti-tubercular drugs rifampicin and isoniazid forces treatment with toxic second-line drugs. Currently, ~4% of new and ~21% of previously treated tuberculosis cases are either rifampicin-drug-resistant or MDR Mtb infections. The specific molecular host-pathogen interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
104
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 52 publications
10
104
0
Order By: Relevance
“…We noticed a distinct shift towards longer DIM chain lengths consistent with the reported increase in molecular mass of DIM during Mtb infection 17 . The residual bacterial contamination of the macrophage membrane fractions was less than 1500 cfu, well below the threshold for detection of DIM extracted directly from bacteria (between 10 5 and 10 7 cfu, see Fig. S1b ).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…We noticed a distinct shift towards longer DIM chain lengths consistent with the reported increase in molecular mass of DIM during Mtb infection 17 . The residual bacterial contamination of the macrophage membrane fractions was less than 1500 cfu, well below the threshold for detection of DIM extracted directly from bacteria (between 10 5 and 10 7 cfu, see Fig. S1b ).…”
Section: Resultsmentioning
confidence: 84%
“…Indeed, Mtb strains lacking DIM are drastically attenuated 3 and are more likely to be killed by the early pulmonary innate immune response 4 , when the bacteria encounter macrophages. Recent work has revealed that DIM modulate macrophage metabolism 5 and immune functions 6, 7 . In particular, DIM increase the ability of Mtb to infect macrophages by modulating phagocytosis 8 , a fundamental immune process involving membrane remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…Many M. tuberculosis-host factors are involved in this first encounter interface at the initial stages of the infection. First, the constitution of the M. tuberculosis cell envelope, which is strain-dependent, from the worldwide used laboratory strains (M. tuberculosis H 37 R a , M. tuberculosis H 37 R v , and M. tuberculosis Erdman), to the highly transmissible CDC1551, to the hypervirulent HN878, and to several relevant drugresistant M. tuberculosis clinical isolates in endemic TB areas (12)(13)(14)(15)(16). We will discuss their cell envelope glycolipid constitution in relation to their infection outcome.…”
Section: Introductionmentioning
confidence: 99%
“…This module contains genes related to transcription and nucleotide synthesis, the known target pathway of Rif (Wishart et al (2017)). Other pathways represented here are lipid metabolism and error-prone synthesis and repair, both known mechanisms of resistance to Rif (Howard et al (2018); Boshoff et al (2003) Table 2: Response TopNets of all 18 drugs are connected graphs with > 50% nodes in a single connected component (CC). In contrast, the graphs induced by the same number of top DEGs, and by randomly sampling the same number of nodes or edges as the TopNet are highly disconnected.…”
Section: Rif Exposure Topnet Reveals the Perturbation Of Nucleotide Smentioning
confidence: 99%